Does metoclopramide exposure alter endometrial receptivity and decrease pregnancy rates? - Çekmez, Yasemin; Korkmaz, Vakkas; Çakır, Aslı; Göçmen, Ahmet; Ergün, Yusuf; Gülşen, Serdar; Akpak, Yaşam Kemal (Taylor & Francis Ltd, 2016)
Objective: The aim of this study was to investigate the effect of metoclopramide on endometrial receptivity with an immunohistochemical investigation of integrin beta 3 expression in pregnant rats. Materials and methods: In the present study, the pregnant mice administrated by different doses of metoclopramide were used to explore the effect of metoclopramide on embryo implantation, especially on the endometrial receptivity. Results: The statistical results showed that the number of implanted embryos was gradually declining along the increasing dose of metoclopramide. When the administrated dose of metoclopramide was 3 mg/kg per day, great changes were observed in the exposed uterine morphology and down-regulated integrin beta 3 were also found in high dose metoclopramide-exposed mice. Conclusion: Metoclopramide exposure, especially in high doses may alter endometrial receptivity by effecting integrin expression on decidual tissue which can decrease pregnancy rates. This drug should only be recommended for use during pregnancy when benefit outweighs the risk.
WOS: 000375027200028
PubMed ID: 26421644
Keywords: Abortion; Decidua; Integrin; Metoclopramide; Pregnancy